2013
DOI: 10.1101/gad.226357.113
|View full text |Cite
|
Sign up to set email alerts
|

The FHA and BRCT domains recognize ADP-ribosylation during DNA damage response

Abstract: Poly-ADP-ribosylation is a unique post-translational modification participating in many biological processes, such as DNA damage response. Here, we demonstrate that a set of Forkhead-associated (FHA) and BRCA1 C-terminal (BRCT) domains recognizes poly(ADP-ribose) (PAR) both in vitro and in vivo. Among these FHA and BRCT domains, the FHA domains of APTX and PNKP interact with iso-ADP-ribose, the linkage of PAR, whereas the BRCT domains of Ligase4, XRCC1, and NBS1 recognize ADP-ribose, the basic unit of PAR. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
168
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(181 citation statements)
references
References 106 publications
4
168
2
2
Order By: Relevance
“…S9A). This is consistent with other findings that PAR also mediates the fast recruitment of other DNA damage repair factors to DNA lesions (15,16). To examine the nature of the relatively fast DNA damage repair mediated by hSSB1, we used siRNA to deplete XRCC1, a key factor for ssDNA damage repair (33-37).…”
Section: Ints3supporting
confidence: 60%
See 2 more Smart Citations
“…S9A). This is consistent with other findings that PAR also mediates the fast recruitment of other DNA damage repair factors to DNA lesions (15,16). To examine the nature of the relatively fast DNA damage repair mediated by hSSB1, we used siRNA to deplete XRCC1, a key factor for ssDNA damage repair (33-37).…”
Section: Ints3supporting
confidence: 60%
“…Thus, INTS3 associates with other partners at DNA lesions to stabilize the hSSB1-INTS3 complex. This biological setting is very similar to the BRCA1/BARD1 complex and the FHA/BRCT domain of NBS1, in which one module interacts with PAR for the fast recruitment to DNA damage sites, whereas the other module is responsible for the prolonged retention at DNA lesions (15,16). Both activities are important for DNA damage repair.…”
Section: Ints3mentioning
confidence: 88%
See 1 more Smart Citation
“…A third module has been described as a PAR binding zinc finger motif (51). Furthermore, for proteins with WWE, BRCT, or FHA domains, it has been demonstrated that their recruitment to sites of DNA damage depends on PAR binding (13,54). Examination of the primary sequence of each of the human RecQ helicases reveals that they have multiple versions of the PBM-type motif, and the motifs of RECQL5 are shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This docking site serves to integrate diverse cellular signaling pathways, including DNA damage detection and repair, transcription, chromatin remodeling, and cell death (11). PAR formation plays a critical role in the rapid recruitment of DNA repair proteins such as MRE11 (12), NBS1 (13), BRCA1 (14), and ATM (15) to DSBs. Mice lacking PARP1 are extremely sensitive to genotoxic stresses, show defects in the repair of damaged DNA, and display genomic instability, with high frequencies of sister chromatid exchange and chromosomal breakage (16).…”
mentioning
confidence: 99%